HUKUM ADAT MINANGKABAU SEBAGAI BASIS DAN PERSPEKTIF DALAM PEMBENTUKAN SISTEM HUKUM NASIONAL - Annisa Wahid (JISRAH: Jurnal Integrasi Ilmu Syariah, 2023)
Minangkabau Customary Law is a traditional legal system that has been developed and passed down through generations within the Minangkabau community in West Sumatra, Indonesia. Rooted in local customs and culture, Minangkabau Customary Law has significant potential to serve as a basis and important perspective in the formation of an inclusive and sustainable national legal system. This research aims to explore the role of Minangkabau Customary Law in the formation of the national legal system and its potential contributions in creating social justice, preserving cultural diversity, and strengthening local autonomy. The research methodology employed is literature analysis, drawing on relevant primary and secondary sources including legal documents, academic writings, and practical experiences in the application of Minangkabau Customary Law. The findings of this research indicate that Minangkabau Customary Law encompasses interconnected principles such as musyawarah-mufakat (consensus-building), gotong royong (community cooperation), and restorative justice. These principles hold universal values that can be adapted and integrated into a broader national legal system. In the context of forming the national legal system, Minangkabau Customary Law can serve as a source of inspiration to develop legislation that aligns with societal interests, protects individual and group rights, and maintains a balance between national and local interests. Furthermore, Minangkabau Customary Law has the potential to preserve cultural diversity in Indonesia. In an era of globalization that often promotes cultural homogenization, the implementation of Minangkabau Customary Law can serve as a strong foundation to promote and safeguard cultural diversity at the national level. Through an approach that respects and acknowledges cultural differences, the national legal system can become an instrument that strengthens cultural identities and ensures the continuity of valuable cultural heritage.